The performance of clinical risk scores in the diagnosis of necrotising fasciitis. (2nd May 2023) - Daniels, Marc; Perbix, Walter; Oberländer, Henrik; Schiefer, Jennifer; Fuchs, Paul Christian; Seyhan, Harun
Abstract : Objective: Necrotising fasciitis (NF) is a quickly progressing and potentially life-threatening infection, involving the fascia and subcutaneous tissues. The diagnosis of this disease is challenging, especially due to a lack of specific clinical signs. In order to ensure a better and quicker identification of NF patients, a laboratory risk indicator score has been developed for NF (LRINEC). A variant has widened this score by adding clinical parameters (modified LRINEC). This study shows current outcomes of NF and compares the two scoring systems. Methods: This study was conducted between 2011 and 2018, and included patient demographics, clinical presentations, sites of infection, comorbidities, microbiological and laboratory findings, antibiotic therapies and LRINEC as well as modified LRINEC scores. The primary outcome was in-hospital mortality. Results: A cohort of 36 patients, diagnosed with NF, were included in this study. The mean hospital stay was 56 days (±38.2 days). The mortality rate in the cohort was 25%. The sensitivity of the LRINEC score was 86%. Calculation of the modified LRINEC score showed an improvement of the sensitivity to 97%. The average LRINEC score and modified LRINEC score for patients who died and who survived were equal (7.4 versus 7.9 and 10.4 versus 10.0, respectively). Conclusion: The mortality rate of NF remains high. The modified LRINEC score increased the sensitivity in our cohort to 97%, and this scoring system could be supportive in the diagnosis of NF for early surgical debridement.